Supporting the Influence of Psychological Capital and Transformational Leadership on Organizational Citizenship Behavior - Felani, Herman Oddyansyah; Nugroho, Sukmo Hadi (LPPM Universitas Trunojoyo Madura, 2023)
This action research aims to find out whether psychological capital and transformational leadership affect organizational citizenship behavior through work engagement with employees of a pharmaceutical packaging-based company in Bekasi. The data collection method in this study used survey methods and distributed questionnaires, respondents were selected by purposive sampling method. the criteria were permanent employees who worked in the same company based on the packaging of medicines located in Bekasi and have worked for at least the last 1 year. The number of samples used was 218 people. The analytical method used is the analysis structural equation model (SEM). The findings from this study were psychological capital, transformational leadership's positive and significant effect on work engagement, and work engagement's positive and considerable influence on organizational citizenship behavior. But psychological capital and transformational leadership does not affect organizational citizenship behavior. Besides that, psychological capital and transformational leadership have positive and significant effects on organizational citizenship behavior through work engagement. In addition, the results found that work engagement can mediate the influence between psychological capital and transformational leadership on organizational citizenship behavior.